2012
DOI: 10.5560/znb.2012-0202
|View full text |Cite
|
Sign up to set email alerts
|

Condensation Reactions of 2-Aminobenzohydrazide with Various Carbonyl Compounds

Abstract: Technical iodine was found to catalyze the condensation between 2-aminobenzohydrazide (1) and some aldehydes and ketones in absolute ethanol under mild conditions to afford hydrazone and quinazoline derivatives, respectively. Condensation of 1 with terephthalaldehyde (2) in 1 : 1 molar ratios afforded the hydrazone 3, while hydrazone 4 was formed on using a double molar ratio of 1. On the other hand, compound 1 condensed with 4-formyl [2.2]paracyclophane (5) to give the hydrazone 6. However, spiro-quinazolines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The racemic ligand was successfully synthesized as shown in Scheme 1. According to the literature, 51 Scheme 2 outlines a rational pathway for the formation of L. Condensation of pyridine-3-carboxaldehyde (2-aminobenzoyl) hydrazone with pyridine-4-carboxaldehyde in boiling ethanol affords a bis-Schiff base intermediate. The racemic ligand is obtained after the nucleophilic attack of the α-nitrogen atom on the iminecarbon atom followed by a 1,3-H shift.…”
Section: Synthesis and Characterization Of Ligand Lmentioning
confidence: 99%
“…The racemic ligand was successfully synthesized as shown in Scheme 1. According to the literature, 51 Scheme 2 outlines a rational pathway for the formation of L. Condensation of pyridine-3-carboxaldehyde (2-aminobenzoyl) hydrazone with pyridine-4-carboxaldehyde in boiling ethanol affords a bis-Schiff base intermediate. The racemic ligand is obtained after the nucleophilic attack of the α-nitrogen atom on the iminecarbon atom followed by a 1,3-H shift.…”
Section: Synthesis and Characterization Of Ligand Lmentioning
confidence: 99%
“…Compounds 102a and 102b were obtained in 70 and 75% yields aer briey maintaining hydrazides 99c and the appropriate aldehyde in aqueous alcoholic solution at 25 C. 68 Continued research into the synthesis of benzo-1,2,4thiadiazepines 102c-l was reported using the same previous reaction conditions and reactants. 70 It was reported that the reaction between amidrazones 107af with 1,4-dioxo-1,4-dihydronaphthalene-2,3-dicarbonitrile (108) in dry ethyl acetate under N 2 atmosphere for a few minutes yielded, aer chromatographic purication and recrystallization, compounds 109a-f (66-80%) (Scheme 23). 71 Various benzene-fused triazepine and triazepinone derivatives were synthesized that showed a variety of biological activities.…”
Section: Tautomerismmentioning
confidence: 99%